Effect of MMR Vaccination to Mitigate Severe Sequelae Associated With COVID-19: Challenges and Lessons Learned - Noverr, Mairi C.; Yano, Junko; Hagensee, Michael E.; Lin, Hui-Yi; Meyaski, Mary C.; Meyaski, Erin; Cameron, Jennifer; Shellito, Judd; Trauth, Amber; Fidel, Jr., Paul L. (Medical Research Archives, 2023)
Mortality in COVID-19 cases was strongly associated with progressive lung inflammation and eventual sepsis. There is mounting evidence that live attenuated vaccines commonly administered during childhood, also provide beneficial non-specific immune effects, including reduced mortality and hospitalization due to unrelated infections. It has been proposed that live attenuated vaccine-associated non-specific effects are a result of inducing trained innate immunity to function more effectively against broader infections. In support of this, our laboratory has reported that immunization with a live attenuated fungal strain induces a novel form of trained innate immunity which provides protection against various inducers of sepsis in mice via myeloid-derived suppressor cells.  Accordingly, we initiated a randomized control clinical trial with the live attenuated Measles, Mumps, Rubella (MMR) vaccine in healthcare workers in the greater New Orleans area aimed at preventing/reducing severe lung inflammation/sepsis associated with COVID-19 (ClinicalTrials.gov Identifier: NCT04475081). Included was an outcome to evaluate the myeloid-derived suppressor cell populations in blood between those administered the MMR vaccine vs placebo. The unanticipated emergency approval of several COVID-19 vaccines in the midst of the MMR clinical trials eliminated the ability to examine effects of the MMR vaccine on COVID-19-related health status. Unfortunately, we were also unable to show any impact of the MMR vaccine on peripheral blood myeloid-derived suppressor cells due to several inherent limitations (low percentages of blood leukocytes, small sample size), that also included a collaboration with a similar trial (CROWN CORONATION; ClinicalTrials.gov Identifier: NCT04333732) in St. Louis, MO. In contrast, monitoring the COVID-19 vaccine response in trial participants revealed that high COVID-19 antibody titers occurred more often in those who received the MMR vaccine vs placebo. While the trial was largely inconclusive, lessons learned from addressing several trial-associated challenges may aid future studies that test the non-specific beneficial immune effects of live attenuated vaccines.